One Laryngospasm, 2 Realities: A Case Report Highlighting the Impact of Data Granularity on Post Hoc Analysis of Perioperative Events. Issue 11 (1st December 2018) - Simpao, Allan F.; Ma, Annie A.; Tan, Jonathan M.; Wasey, Jack O.; Masino, Aaron J.; Gálvez, Jorge A.
Abstract : We present the case of a laryngospasm event in a 21-month-old child in which the changes in pulse oximetry and end-tidal carbon dioxide were recorded by both our Anesthesia Information Management System and middleware medical device integration platform. When this case was analyzed retrospectively, we noted that the 2 systems recorded the event very differently with respect to pulse oximetry. This case report illustrates the impact of data sampling rates on post hoc analysis of perioperative events and highlights the importance of understanding data collection processes when using electronically recorded data.